“Fit to Kill”: A Case Report on Undiagnosed Temporal Lobe Epilepsy Leading to Homicide - Indu Surendran; Scott Broadhurst; Inti Qurashi (BJPsych Open)
Aims: Temporal Lobe Epilepsy (TLE) is the most common symptomatic cause of partial epilepsy worldwide. It can present with vague symptoms including affective disturbances, personality changes, sensory disturbances, altered consciousness etc., which can confound diagnosis. Overt focal or tonic-clonic seizures are present in only 60% patients. It manifests with psychotic symptoms in around 5%. This case report describes how undiagnosed TLE with psychotic symptoms led to grave consequences.